Merck and Vioxx. (B), Merck settled claims for $4.85 billion - Elias, Jaan, (SAGE knowledge. Cases., 2016)
Backing off their strategy to fight every single claim, Merck & Co. reached a settlement with a steering committee of plaintiffs' attorneys in November 2007. According to the agreement, the company would pay $4.85 billion to settle most claims arising from its Vioxx medication. Merck stressed that the settlement was not a class action. In addition, Merck did not admit to any fault in its sale of Vioxx. Lawsuits that had already gone to verdict would not be affected by the settlement. This study details the process of the legal settlement.